2022
DOI: 10.3390/molecules27165340
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Soil Mercury by Modified Vermiculite-Montmorillonite and Its Effect on the Growth of Brassica chinensis L.

Abstract: In this study, the surface of vermiculite-montmorillonite was modified by MnO2 loading. The modified vermiculite-montmorillonite was added to remediate the potentially toxic trace element (PTE) Hg present in soil containing coal gangue. Pot experiments were conducted to analyze and compare the pH values, Hg contents and Hg species present in coal gangue-containing soil, with and without the modified materials added, to determine whether the addition of modified materials had an effect on the growth of Brassica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Wang et al, (2012) studied mercury metal extraction from contaminated soil using different types of plant species [ 148 ]. Li et al, (2022) observed that the addition of 15 g/kg of modified vermiculite-montmorillonite reduces 98.2% mercury concentration from polluted soil samples [ 149 ].…”
Section: Different Techniques Employed For the Removal Of Hmis Fromhm...mentioning
confidence: 99%
“…Wang et al, (2012) studied mercury metal extraction from contaminated soil using different types of plant species [ 148 ]. Li et al, (2022) observed that the addition of 15 g/kg of modified vermiculite-montmorillonite reduces 98.2% mercury concentration from polluted soil samples [ 149 ].…”
Section: Different Techniques Employed For the Removal Of Hmis Fromhm...mentioning
confidence: 99%
“…Li et al [36] used MnO 2 loading on vermiculite-montmorillonite to remove Hg in contaminated soils. They found that adding 15 g/kg of modified vermiculite-montmorillonite reduced the Hg concentration in the soil to 98.2%.…”
Section: Soil Pollutionmentioning
confidence: 99%
“…Coal gangue (CG), a solid waste from coal mining and processing, has low carbon content and high hardness [ 1 , 2 ]. Notably, the annual generation of CG solid waste reaches up to 37–550 million tons [ 3 ], and its effective utilization is still less than 15% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%